2018
DOI: 10.4143/crt.2017.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Features and Outcomes in Epithelial Ovarian Cancer according to Tumorigenicity in Patient-Derived Xenograft Models

Abstract: PurposeAlthough the use of xenograft models is increasing, few studies have compared the clinical features or outcomes of epithelial ovarian cancer (EOC) patients according to the tumorigenicity of engrafted specimens. The purpose of this study was to evaluate whether tumorigenicity was associated with the clinical features and outcomes of EOC patients. Materials and MethodsEighty-eight EOC patients who underwent primary or interval debulking surgery from June 2014 to December 2015 were included. Fresh tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…22 Similar results have been described for a variety of tumor types, including colorectal cancer, breast cancer, and ovarian cancer. [37][38][39] Our study had similar findings with significant reductions in recurrence free survival for patients with successful PDX models. This positive correlation presents an opportunity to identify patients who are at a high risk for recurrence following their resection and also an opportunity to utilize the derived PDX tumors to identify potential therapies for clinical use prior to documented clinical recurrence.…”
Section: Discussionsupporting
confidence: 79%
“…22 Similar results have been described for a variety of tumor types, including colorectal cancer, breast cancer, and ovarian cancer. [37][38][39] Our study had similar findings with significant reductions in recurrence free survival for patients with successful PDX models. This positive correlation presents an opportunity to identify patients who are at a high risk for recurrence following their resection and also an opportunity to utilize the derived PDX tumors to identify potential therapies for clinical use prior to documented clinical recurrence.…”
Section: Discussionsupporting
confidence: 79%
“…Certainly, there was still controversial about the relationship between tumor type and TFR of PDX models. Previous studies reported that the TFR of PDX models in high‐grade serous ovarian cancer was higher than low‐grade serous ovarian cancer . While another author insisted that there was no relationship between tumor type and TFR of PDX models, so the relationship between tumor type and TFR of PDX models still needed larger sample size to verify.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported that the TFR of PDX models in high-grade serous ovarian cancer was higher than low-grade serous ovarian cancer. 15,31 While another author insisted that there was no relationship between tumor type and TFR of PDX models, 18 so the relationship between tumor type and TFR of PDX models still needed larger sample size to verify. In addition, previous studies have reported that the immunodeficient degree of experimental animals, the location of tumor derived, and the transplanted location of cancer were another important factors for TFR of PDX models.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was systematically observed in all studies and offered the opportunity to evaluate a possible link between tumor growth in xenotransplantation assay and biological properties of ovarian cancers. Thus, two recent studies based on xenotransplantation of patient’s derived fresh ovarian tumor tissues xenografted either subcutaneously or in the subrenal capsule showed that patients whose tumors became engrafted have reduced progression survival and overall survival, compared to patients whose tumors failed to engraft [ 322 , 323 ]. These observations suggest that xenograft models can be useful as a preclinical tool to predict prognosis.…”
Section: Mouse Models Of Human Epithelial Ovarian Cancermentioning
confidence: 99%